Pemanfaatan Lem Bakar untuk Aksesoris Kuku 3D Nail Art - Tiara Irawati; Kuswidyaningrum Naharina Jannati; Agus Susanti (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2024)
This study uses hot glue as the main material for making 3D nail art accessories because of its ease of formation and its potential to reduce nailist dependence on 3D accessory techniques. The author made 3D nail art accessories with and without tool molding, with the aim of understanding the manufacturing process, assessing feasibility, and evaluating the level of public preference for this product. This study used observation, literature, documentation, questionnaire, experiment, and qualitative descriptive analysis methods. The results of the second experiment showed that nail art products from hot glue had high feasibility, with the highest scores on the color indicators (14), adhesion (15), and neatness (14), and designs that received a decent score (13). Public tests from 30 respondents showed a high level of agreement on the aspects of color (4.3), adhesion (3.9), neatness (4.3), and design (4.2). The process of making 3D nail art accessories from hot glue using tool molding involved applying baby oil, shooting hot glue, and cutting with scissors. This study suggests the need for further research to improve the design and color variations of 3D nail art accessories made from hot glue.